2005
DOI: 10.1128/jvi.79.23.14614-14621.2005
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Receptor Expression and Severe Acute Respiratory Syndrome Coronavirus Infection Depend on Differentiation of Human Airway Epithelia

Abstract: Studies of patients with severe acute respiratory syndrome (SARS) demonstrate that the respiratory tract is a major site of SARS-coronavirus (CoV) infection and disease morbidity. We studied host-pathogen interactions using native lung tissue and a model of well-differentiated cultures of primary human airway epithelia. Angiotensin converting enzyme 2 (ACE2), the receptor for both the SARS-CoV and the related human respiratory coronavirus NL63, was expressed in human airway epithelia as well as lung parenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
817
2
23

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 885 publications
(911 citation statements)
references
References 50 publications
42
817
2
23
Order By: Relevance
“…Tissue expression of the receptor correlates with the localization of the virus in infected individuals and animals. 22,47,61,62 In addition, the efficiency of infection is correlated with the ability of the ACE2 within each species to support viral replication. A study of ACE2 knockout mice indicated that the enzyme is a crucial receptor for SARS-CoV in vivo 24 and that SARS-CoV and the S protein both reduce ACE2 expression.…”
Section: Role Of Ace2 In the Pathogenesis Of Sarsmentioning
confidence: 99%
“…Tissue expression of the receptor correlates with the localization of the virus in infected individuals and animals. 22,47,61,62 In addition, the efficiency of infection is correlated with the ability of the ACE2 within each species to support viral replication. A study of ACE2 knockout mice indicated that the enzyme is a crucial receptor for SARS-CoV in vivo 24 and that SARS-CoV and the S protein both reduce ACE2 expression.…”
Section: Role Of Ace2 In the Pathogenesis Of Sarsmentioning
confidence: 99%
“…ACE2 is predominantly expressed on the apical surface of well-differentiated airway epithelia, especially ciliated cells (30,56). Since a virus must attach to and enter cells before it can replicate, surface expression of ACE2 and the state of cell differentiation may directly influence SARS-CoV disease pathogenesis (30).…”
mentioning
confidence: 99%
“…Viral infectivity of airway epithelia is often polarized and correlates with differential expression of corresponding viral receptors. For example, 229E and severe acute respiratory syndrome coronaviruses infect human airway epithelia at higher efficiency from the apical surface, and this correlates with predominant apical expression of their receptors, aminopeptidase N (CD13) and angiotensin-converting enzyme 2 (15,33). In contrast, adenoviruses infect human airway epithelia best from the basolateral surface, which correlates with Coxsackie virus and adenovirus receptor segregation to the basolateral surface (34).…”
Section: Discussionmentioning
confidence: 99%
“…The basolateral or apical surfaces of airway epithelia were selectively treated with 1 mg/ml N-hydroxysulfosuccinimidobiotin (Pierce) in PBS for 30 min at 25°C as described previously (15). The epithelial surface was washed and then incubated with 100 mM glycine in PBS for 20 min at 25°C to quench unreacted biotin.…”
Section: Surface Protein Isolationmentioning
confidence: 99%
See 1 more Smart Citation